UPAYA PENYULUH AGAMA ISLAM DALAM MEMBINA REMAJA BERPERILAKU MENYIMPANG DI DESA BALANGTANAYA KECAMATAN POLONGBANGKENG UTARA KABUPATEN TAKALAR (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
This study discusses the efforts of Islamic extension agents in fostering adolescents with deviant behavior in Balangtanaya Village, Polongbangkeng Utara District, Takalar Regency. Factors that cause adolescents to drink alcoholic deviant behavior in Balangtanaya Village, Polongbangkeng Utara District, Takalar Regency. This article also discusses the method of Islamic extension agents in fostering adolescents with deviant behaviors to drink alcoholic beverages in Balangtanaya Village, Polongbangkeng Utara District, Takalar Regency. The results of the study show that the method of Islamic extension agents in their efforts to foster adolescents with deviant behavior drinking alcohol in Balangtanaya Village, Polongbangkeng Utara District, Takalar Regency pursued through several methods, namely the method of lectures conducted in mosques and recitation of majelis taklim, the method of education/teaching at TKA / TPA and the method of Uswatun hasanah / exemplary. The supporting factors for the Islamic religious extension in the effort to foster adolescents with deviant behavior in Balangtanaya Village, Polongbangkeng Utara District, Takalar Regency, are the personality of the Islamic religious instructor, the professionalism of the Islamic religious instructor, and the condition of adolescents.